Metodiceskie podchody k issledovaniju dvigatel'nogo ritma v machovych dvizenijach - Goverdovskij, V. I.; Terent'eva, O. S. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The authors assumed, that the data received as the result of the complex research, will specify representations either about technique of considered exercises, and, in particular, about their rhythmic structure and will be the basis for the development of training programs, that as a whole will result in the optimization of the process of mastering by base exercises on a horizontal bar.